Želod in žir sta bila pomembna postranska gozdna proizvoda - Perko, Franc (Gozdarski vestnik, 2014)
In the past, acorn and beechnut were important forest by-products. When oak and beech were bearing fruits, farmers drove pigs into forests and thus fattened them additionally. Acorn was also ground in acorn flour used for bread; it was also roasted and used as coffee substitute, acorn spirit ŽhrastovecŽ was also made from it. Beechnut was used for pressing quality edible oil. Beechnut contains 20 to 30 percent of fats, the cores even from 30to 40 percent. By pressing we extract up to 80 percent of fats. From 100 kg of beechnut (70 kg of fruits) we become around twelve liters of oil. Authorities encouraged and supported gathering beechnut for edible oil especially in times of war and after-war crises, when purchase of food was limited. After pressing, oilcakes remain; they are good pig and chicken fodder. In small amounts they are also allowed to be used as cattle fodder, however, beechnut oil cakes are not usable for horses. Today, as the interest in ecologically produced foods is increasing, quality edible oil could be produced bearing in mind rich beechnut harvests.
Keywords: bukev; Croatian Growth; hrast; žir; želod; jedilno olje; svinjska paša; postranski gozdni proizvodi